NUMBERED HEADS TOGETHER LEARNING STRATEGY FOR INCREASING FRESHMEN STUDENTS’ ACHIEVEMENT IN LITERATURE THEORY COURSE - Fina Hiasa; Emi Agustina (JOALL (Journal of Applied Linguistics and Literature), 2020)
This study aims to find out how the implementation of the Numbered Heads Together (NHT) learning model in Literature Theory courses can improve the quality of learning. The subject of this research is the first semester students of class B TA 2019/2020 Indonesian Language Education Study Program FKIP Unib who are taking Literature Theory courses. Data collection techniques were carried out through questionnaires conducted in cycles I and II. It also used a test technique in the form of an oral test in cycles I and II. The study was conducted in two cycles. In the second cycle the expected learning outcomes are achieved. Learning outcomes in the second cycle showed that of 40 students there were 15 students (37.5%) who received an A. As many as 20 students with B (50%). The rest is a C value of 5 people (12.5%) and a D value of 0 people (0%). Keywords: Numbered Heads Together, Literary Theory